Redescription of Hippasa deserticola, the northernmost species of Hippasa (Aranei: Lycosidae), with taxonomic notes on other species of the genus Переописание Hippasa deserticola, самого северного вида рода Hippasa (Aranei: Lycosidae), с замечаниями по систематике других видов рода - Marusik Yuri M.; Nadolny Anton A. (Russian Academy of Sciences, Zoological Institute, 2022)
Hippasa deserticola Simon, 1889, stat. resurr., thought to be a synonym of H. partita (O.Pickard-Cambridge, 1876) is revalidated and redescribed. Two names, Trochosa loeffleri Roewer, 1955, syn. nov., and H. afghana Roewer, 1960, syn. nov., are synonymised with H. deserticola; H. cinerea Simon, 1898, syn. nov., is synonymised with H. partita. The distribution of H. deserticola is mapped based on the published data and the specimens examined. The embolic division and the tegular apophysis in two species belonging to different species groups are illustrated for the first time as well as modification of cuticle on the tibiae. The taxonomic status of H. partita is briefly discussed.